Critical Chorography: A Pedagogical Approach. Issue 1 (March 2018) - Cohen, Jason E.
Abstract : This essay articulates the concept of 'critical chorography' through a discussion of the productive intersection of pedagogy in the spatial humanities and map theory as applied to the visualization of early modern maps using contemporary GIS technology. In method, the essay lays out a comparative model for the analysis of maps across early modern and contemporary digital practices by theorizing student-driven practices of mapping first through a deep attention to historical location and documentary evidence, and second, through an inquiry into the digital implications of mapping jurisdictional conflicts through case studies focused on westward expansion in the West Indies. To those ends, the essay examines the drive in contemporary spatial humanities to use the map as a tool of analysis, rather than merely as a platform for visualization and presentation.